O uso da racionalidade substantiva no gerenciamento de impressão em relatórios socioambientais - Silva, Letícia Bechara (2021)
Objective: This paper aims to investigate a predominant rational approach in the use of impression management in the accounting narratives of Samarco Mineração S.A. and Fundação Renova, through the lens of Legitimacy Theory. Methodology: The study is characterized as qualitative, carried out through descriptive and explanatory research. The content analysis was based on the Management's Statement of the sustainability reporting of Samarco Mineração S.A. and the Fundação Renova for the year 2019, related to the disaster that occurred in Mariana-MG in 2015, caused by the collapse of the Samarco‟s dam. The categories used were adapted from the literature based on the studies by Serva (1996) and Tedeschi & Melburg (1984 as cited in Ogden & Clarke, 2005, p. 322), which refer to instrumental and substantive rationalities and impress management. Results: The results suggest that substantive rationality are predominat in Renova‟s report, however it was applied to the same extent as instrumental rationality in Samarco‟s report. Based on the literature and data analysis, it is inferred that this is due to Samarco having used the strategy of distancing itself from the negative event, thus blaming Renova for the reparatory actions. Contributions: This research allowed the analysis of differences and similarities between company reports related to environmental disasters and seeks to contribute to the advancement of the Legitimacy Theory, as it shows the importance of the use of socioenvironmental and economic-financial aspects for socio-environmental disclosure, thus assisting the construction, restore or maintenance of organizational legitimacy.